(untitled) (International Journal of Innovative Technologies in Economy, 2019)
Modern marketers use the latest scientific achievements in their work. One of the new techniques in their practice is called neuromarketing. It involves scanning consumers’ brains while viewing ads and consuming products. The article highlights the concept of neuromarketing, its scope, methods and directions of neuromarketing in the modern world, as well as some examples of the use of neuromarketing.